ABC energies and spectral radii of some graph operations - Bilal, Ahmad; Munir, Muhammad Mobeen (Frontiers in Physics, 2022)
The present article presents some new results relating to Atomic Bond Connectivity (ABC) energies and Spectral Radii of generalized splitting and generalized shadow graphs constructed on the basis of some fundamental families of graphs cycle graph Cn, complete graph Kn and complete bipartite graph Kn,n referred as base graphs. In fact we relate the energies and Spectral Radii of splitting and shadow graphs with the energies and Spectral Radii of original graphs